The Northeastern Palaearctic light coloured Neocrepidodera Heikertinger, 1911 (Coleoptera: Chrysomelidae), with description of a new species - Baselga, Andrés (Zootaxa, 2006)
The light coloured Neocrepidodera Heikertinger from East Siberia are reviewed. Six species are recognized in this region, including the newly described N. konstantinovi sp. nov. and the new record of N. motschulskii (Konstantinov) from Primorskiy Kray that represents a major range extension. A neotype is designated for N. sublaevis (Motschulsky) and a re-description is provided for this species. A diagnosis along with figures of pronotum, aedeagus, vaginal palpi and spermatheca are presented for all species, and a key for the Eastern Siberian light coloured taxa is provided.